A new configuration for planar magnetic elements to reduce capacitive couplings - Shahabi, N.; zare, F.; Ghosh, Arindam; Ledwich, G. (Institute of Electrical and Electronics Engineers ( IEEE ), 2010)
This paper presents an analysis of planar magnetic element configurations in order to reduce capacitive couplings between the windings. The investigation and simulation results, both 2D and 3D Finite Element (FE) show the effect of shifting the planar layers in reduce the capacitive couplings. The simulation results are compared with test results to validate the proposition.